2014
DOI: 10.3390/s140813730
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Relaxor-Based Ferroelectric Single Crystals for Ultrasonic Transducer Applications

Abstract: Relaxor-based ferroelectric single crystals Pb(Mg1/3Nb2/3)O3-PbTiO3 (PMN-PT) have drawn much attention in the ferroelectric field because of their excellent piezoelectric properties and high electromechanical coupling coefficients (d33∼2000 pC/N, kt∼60%) near the morphotropic phase boundary (MPB). Ternary Pb(In1/2Nb1/2)O3-Pb(Mg1/3Nb2/3)O3-PbTiO3 (PIN-PMN-PT) single crystals also possess outstanding performance comparable with PMN-PT single crystals, but have higher phase transition temperatures (rhombohedral t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(24 citation statements)
references
References 73 publications
(89 reference statements)
2
22
0
Order By: Relevance
“…Second generation crystals extend the high electromechanical properties to a broader range of temperature, electric field and mechanical stress, expanding their design envelope by reducing the need for heat shunts and applied dc fields. Crystals with higher ferroelectric phase transition temperatures and higher coercive fields are in this category [141,153,275,278], where the potential commercialization of the ternary PIN-PMN-PT and PMN-PZT is expected. Third generation crystals include the addition of small amount of dopants to tailor the crystal’s electromechanical parameters in order to meet specific device requirements.…”
Section: The Development Of Relaxor-pt Single Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second generation crystals extend the high electromechanical properties to a broader range of temperature, electric field and mechanical stress, expanding their design envelope by reducing the need for heat shunts and applied dc fields. Crystals with higher ferroelectric phase transition temperatures and higher coercive fields are in this category [141,153,275,278], where the potential commercialization of the ternary PIN-PMN-PT and PMN-PZT is expected. Third generation crystals include the addition of small amount of dopants to tailor the crystal’s electromechanical parameters in order to meet specific device requirements.…”
Section: The Development Of Relaxor-pt Single Crystalsmentioning
confidence: 99%
“…4 shows a Relaxor-PT single crystal boule grown by the Bridgman method, which can be separated into three different composition phases, including R phase, O/M (monoclinic) phase and T phase along the growth direction, due to the large segregation coefficient of Ti 4+ [153,187,207]. It was observed that the crystals exhibit 4mm macroscopic symmetry when the crystals were poled along [001] directions, with engineered domain configurations 4R and 4O in R and O phase crystals respectively, while single domain state 1T is presented in T phase crystals.…”
Section: The Development Of Relaxor-pt Single Crystalsmentioning
confidence: 99%
“…A number of authors have estimated the elastic parameters of cylindrical sample using the first break travel time and phase velocity methods (Simons, 1987;Vernik, 1994;Lee and Waite, 2009;Chen et. al., 2014;Shragge, J. et.…”
Section: Introductionmentioning
confidence: 99%
“…Piezocrystals are now used widely in biomedical ultrasound imaging and investigation of their possibilities is under way in nondestructive evaluation, particle manipulation and underwater sonar [7][8][9][10] based on piezoelectric properties including k 33 ≈ 90% and d 33 > 1500 pC/N [11]. Bulk, monolithic piezocrystal has little advantage over piezoceramic, with the values of k t being similar, but improved performance can be realized in configurations such as the planks used in biomedical imaging arrays and the pillars used in piezocomposites.…”
Section: Introductionmentioning
confidence: 99%